Boosting Work Productivity: The Impact of Supportive Leadership, Work Motivation, and Discipline in UMKM Aldiva Maju Jaya: Meningkatkan Produktivitas Kerja: Dampak Kepemimpinan yang Mendukung, Motivasi Kerja, dan Disiplin di UMKM Aldiva Maju Jaya - Lia, Ria Nova; Firdaus, Vera (Universitas Muhammadiyah Sidoarjo, 2023)
This study aimed to investigate the relationships between supportive leadership, work motivation, discipline, and work productivity among employees of UMKM Aldiva Maju Jaya. The research collected primary data through the distribution of questionnaires to 100 employees and used SmartPLS 3.0 program to analyze the data. The results of the validity test indicated that all statements in the questionnaire were valid, while the reliability test showed that only one variable had a reliable composite reable value or Cronbach’s Alpha value. The hypothesis tests indicated that supportive leadership, work motivation, and discipline had significant effects on work productivity. The study implies that improving supportive leadership, work motivation, and discipline can lead to enhanced work productivity among UMKM Aldiva Maju Jaya employees. Highlights: The study investigated the impact of supportive leadership, work motivation, and discipline on work productivity among employees of UMKM Aldiva Maju Jaya. The research used primary data collected through questionnaires and analyzed using SmartPLS 3.0 program. The study found that improving supportive leadership, work motivation, and discipline can lead to enhanced work productivity among UMKM Aldiva Maju Jaya employees.